Laminação em atmosfera inerte de ligas à base de magnésio para armazenagem de hidrogênio - Lago, Milton Luis do (2014)
In recent decades, the use of energy presented strong growth due to the need of supplying the daily energy consumption of approximately seven billion people. To solve this problem, it has been investigated the nature, alternative energy sources which respect the environmental issues, to provide social and technological development without negative impacts on the environment. Several processing routes have been investigated in recent years in order to overcome the obstacles of storage and availability of hydrogen as a clean, safe, cost effective and of easy manipulation energy source. The solid state reaction of magnesium and hydrogen gas produces the magnesium hydride compound which provides safe manipulation, high volumetric and gravimetric densities when compared to other traditional forms of storage (liquid or gas), coming out to be promising for being used on an industrial scale as energy carrier for mobile application. However, conventional processing routes produce a material which requires the use of high temperatures during cycling, as well as low speed of the kinetics of absorption and desorption of hydrogen gas, which limits its possibility of application. This work aims to improve the properties of magnesium alloys by cold rolling under inert atmosphere. To achieve this goal, it was developed a laminator equipped with speed control of cylinders that has capacity of 1.1 kilowatts, which works inside a glovebox. The equipment allows producing, by severe plastic deformation, voluminous magnesium-bases samples to storage hydrogen gas, under controlled atmosphere in order to avoid the incorporation of gaseous and/or solid impurities usually found on other viii routes of processing. Structural characterization of the processed samples was performed by techniques of analysis of XRD, SEM and TEM. The hydrogen storage properties were evaluated by DSC and measurements of PCT.